Penerapan Model Make A Match Untuk Meningkatkan Kosakata Bahasa Arab Pada Siswa Kelas III SDIT Al-Bashirah Palopo - Novitasari, Novitasari; Mawardi; Firman Muhammad Arif; M. Zuhri Abu Nawas; Alfan Putra; Sri Wahyu Widya Nengsi; Hijrawati Emma; Nur Ainun Yasir (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study aims to analyze the effectiveness of the Make A Match learning model in improving Arabic vocabulary mastery on the sports theme among third-grade students of SDIT Al-Bashirah Palopo. The main problem addressed in this study is the low level of students’ vocabulary mastery, which affects their overall language skills. This research employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 17 students. Data were collected through tests, observation, and documentation. The results showed that the average pre-test score of 36.00 increased to 77.06 in the post-test. The paired sample t-test result indicated a significance value of 0.000 < 0.05, meaning there was a significant difference. The novelty of this study lies in the application of the Make A Match model specifically focused on sports-themed vocabulary at the elementary school level, as well as the integration of game-based cooperative activities that enhance student engagement. Therefore, this model is proven effective in improving Arabic vocabulary mastery among elementary school students